FLLL32, a curcumin analog, ameliorates intestinal injury in necrotizing enterocolitis - Eckert J (Dove Medical Press, 2017)
Jeffrey Eckert,1 Brian Scott,1,2 Shelley M Lawrence,3 Michael Ihnat,4 Hala Chaaban1 1Department of Pediatrics, University of Oklahoma Health Sciences Center, Oklahoma City, OK, 2Department of Pediatrics, University of Texas Health Science Center at San Antonio, San Antonio, TX, 3Department of Pediatrics, University of California San Diego, San Diego, CA, 4Department of Pharmaceutical Sciences, University of Oklahoma, College of Pharmacy, Oklahoma City, OK, USA Background: Necrotizing enterocolitis (NEC) is a devastating gastrointestinal disease that primarily affects premature infants. It is characterized by inflammation and leukocyte infiltration that can progress to intestinal necrosis, perforation, systemic inflammatory response, and death. In this study, we examined the effect of FLLL32, a curcumin analog, on an NEC-like neonatal intestinal injury model. Methods: NEC was induced in CD-1 mice pups using the Paneth cell ablation and Klebsiella infection model. Pups were divided into sham, NEC, and NEC + FLLL32 groups. At the end of the experiment, pups were euthanized; whole blood and small intestines were harvested. Intestinal inflammatory cytokine profile, in vivo intestinal permeability using serum fluorescein isothiocyanate-dextran, and histological injury scores were compared between the groups. Results and conclusion: FLLL32-treated pups had lower intestinal injury, improved intestinal permeability, and lower proinflammatory cytokine profiles compared to those in untreated pups with NEC. These results suggest that FLLL32 plays a protective role in NEC. Keywords: necrotizing enterocolitis, neonatal intestinal inflammation, curcumin, FLLL32, STAT3 inhibitors